How respondents' age influence perceptions of socio-economic issues in the context of sustainable local development - Hübel (Anghel), Stefania-Rodica; Stan, Mari-Isabella; Tasente, Tanase (Eximia, 2023)
In the realm of contemporary socio-economic studies, the interplay between age and perceptions of socio-economic issues within the framework of sustainable local development has emerged as an intriguing area of exploration. This research paper explores the impact of respondents' age on their perceptions of socio-economic issues within the context of Sustainable Local Development (SLD). The study involved 216 participants of diverse ages distributions who completed a structured questionnaire. The analysis demonstrates that all ages significantly influence participants' perspectives on various aspects of their lives, including quality of life, future expectations, and attitudes towards societal and economic structures. However, the influence of these demographic variables varies across different areas, highlighting the intricate and nuanced nature of their interplay. Thus, the paper emphasizes the importance of understanding these perceptual differences to develop strategies for SLD that are socially inclusive and responsive. It further suggests the need for further exploration of these relationships to deepen our understanding.